Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T19:20:20+01:00
A)x²-3+4x=(x+2)²-1

x²-3+4x = x²+4x + 4 -1
x²+4x -x² - 4x = 3 +3
0 = 6 sprzeczność
b)- (x+9)/6+2(x²-5)/3=2/3(x-2)²
-(x +9)/6 + 2( x² -10x +25)/3= 2/3(x² - 4x+4) / *6
-x -9 +4(x² -10x +25) = 4(x² - 4x+4)
-x-9 +4x² -40x +100 = 4x² -16x +16
-x+4x² -40x -4x² +16x = 16 - 100+9
-25x = - 75
x = 3
c) ( p-2)²+1=(p-8)/3+(p-1)(p+1)
p² -4p +4 +1 = (p-8)/3 +p² - 1
p² -4p - p² = (p-8)/3 - 1 -5
-4p = (p-8)/3 -6 / *3
-12p = p-8 -18
-12p - p = -18 -8
-13p = -26
p = 2